Hitchcock on Hitchcock. Volume 1, Selected Writings and Interviews. - Hitchcock, Alfred, 1899-1980.; Gottlieb, Sidney (Berkeley : University of California Press, 2015)
Gathered here for the first time are Alfred Hitchcock's reflections on his own life and work. In this ample selection of largely unknown and formerly inaccessible interviews and essays, Hitchcock provides an enlivening commentary on a career that spanned decades and transformed the history of the cinema. Bringing the same exuberance and originality to his writing as he did to his films, he ranges from accounts of his own life and experiences to techniques of filmmaking and ideas about cinema in general. Wry, thoughtful, witty, and humorous-as well as brilliantly informative-this selection reve.
Hitchcock Talks About Lights, Camera, Action (1967)It's a Bird, It's a Plane, It's ... The Birds (1968); Hitchcock at Work (1976); A BIBLIOGRAPHY OF THE WRITINGS OF ALFRED HITCHCOCK; WORKS CITED; INDEX.
Print version record.
eBooks on EBSCOhost
Keywords: Hitchcock, Alfred, -- 1899-1980 -- Interviews; Hitchcock, Alfred, -- 1899-1980; Motion picture producers and directors -- Interviews; Motion pictures -- Production and direction; Cinéma -- Production et réalisation.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion picture producers and directors; Motion pictures -- Production and direction; Interviews